„Der Mensch muß immer Zweck an sich selbst bleiben“: der rechtsethische Vorbehalt gegen die sog. Anatomiekunst - Bleyl, Uwe (Annals of anatomy, 1999)
After 10 years of intensive debate about Gunther von Hagens’ “Body Worlds” exhibition, this article systematically analyses the arguments that have been raised. Two elements of the debate are critical: the donor's self-determination and consideration for the family and acquaintances. However, the arguments for and against the public exhibition of human remains, and the unusual positioning of the figurative plastinates seems to be amenable to discussion and also seems to allow different ethical weighing. Perhaps this can be understood as an indicator that, to start with, discussion is necessary in regard to our general burial culture.